2021
DOI: 10.1080/15248372.2021.1888731
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Theory of Mind and Wishful Thinking in Children’s Moralizing Concepts of the Abrahamic God

Abstract: Robles, Simran Suresh, Aaliyah Triumph, and Haley Ward for assistance with data collection and coding; James Dunlea, Megan Goldring, and Ayse Payir for their feedback; and the Brooklyn Children's Museum, Traphagen Elementary School, and Crescent Elementary School for providing testing space. This project was made possible through the support of grant #61080 from the John Templeton Foundation to LH. The opinions expressed in this publication are those of the authors and do not necessarily reflect the views of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In addition, cross-cultural individual-level studies have found evidence of baseline levels of moralization in people's reasoning about spirits and deities using both item response scales (Purzycki, 2013a; and free-listing (Bendixen et al, nd;Purzycki, 2011Purzycki, , 2016. These findings are corroborated by developmental research showing that young children in Western societies readily attribute moral knowledge to God (e.g., Heiphetz et al, 2016;Wolle et al, 2021).…”
Section: Religion As An Extension Of Evolved Social and Moral Cognitionmentioning
confidence: 89%
“…In addition, cross-cultural individual-level studies have found evidence of baseline levels of moralization in people's reasoning about spirits and deities using both item response scales (Purzycki, 2013a; and free-listing (Bendixen et al, nd;Purzycki, 2011Purzycki, , 2016. These findings are corroborated by developmental research showing that young children in Western societies readily attribute moral knowledge to God (e.g., Heiphetz et al, 2016;Wolle et al, 2021).…”
Section: Religion As An Extension Of Evolved Social and Moral Cognitionmentioning
confidence: 89%
“…Additionally, Japanese 4-to 5-yearolds tend to claim that God has both experience (e.g., can feel things) and agency (e.g., can do things) (Moriguchi et al 2019). Regarding God's moral interests, 4-to 5-year-old children will say that God would have more knowledge of their own, rather than others', prosocial actions, but have more knowledge of others', rather than their own, transgressions (Wolle et al 2021).…”
Section: Religious Agentsmentioning
confidence: 99%
“…Preschoolers often view God's mind as similar to a human mind (e.g., attributing to God only knowledge that they themselves possess; Kiessling & Perner, 2014;Lane et al, 2010Lane et al, , 2012. By six years of age, many children around the world-including US and Spanish children from religious and secular backgrounds, Yukatek Mayan children, and Greek Orthodox children-typically distinguish God's mind from human minds, such as by reporting that God, but not a person, would know what was in a display that was hidden from view (Barrett et al, 2003;Gimenez-Dasi et al, 2005;Knight et al, 2004;Makris & Pnevmatikos, 2007;Wolle et al, 2021). However, this distinction may occur somewhat later in development when considering God's own moral beliefs, as opposed to God's knowledge of factual information.…”
Section: The Intersection Of Intent-based Moral Judgment and Religiou...mentioning
confidence: 99%
“…Work in this area has focused on adults' God concepts (e.g., Johnson et al, 2013;McNamara et al, 2016;Norenzayan, 2013;Purzycki et al, 2012;Spilka et al, 1964), with a smaller number of developmental studies probing children's attributions of factual knowledge to God (e.g., Barrett et al, 2003;Kiessling & Perner, 2014;Knight et al, 2004). One prior study showed that 6-to 7-year-olds attribute greater moral knowledge to God than do 4-to 5-year-olds (Wolle et al, 2021) but did not ask how children expect God to respond to wrongdoing. In addition to extending basic scientific knowledge of God concepts, addressing this question can have translational implications.…”
Section: The Intersection Of Intent-based Moral Judgment and Religiou...mentioning
confidence: 99%
See 1 more Smart Citation